Language Learning Strategies Research in Colombia: A Review of the Last 10 Years: Investigación Sobre Estrategias de Aprendizaje de Idiomas en Colombia: Una Revisión de los Últimos 10 Años - Marenco Domínguez, José Miguel (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2023)
The concept of language learning strategies has been extensively examined to understand the cognitive processes and behaviors aimed at enhancing language performance and proficiency. The selection and instruction of learning strategies may vary due to contextual factors. Considering this, the objective of this literature review is to analyze the current trends in the field of language learning strategies specifically within the context of Colombia. The search methodology employed the keywords “language learning strategies” to identify empirical research conducted in Colombia, which was obtained from the SciELO, ERIC, and Redalyc databases. After the rigorous selection process, a shortlist of 13 relevant documents was compiled. The findings of this review reveal that learning strategies have been mainly explored using a qualitative lens with small sample sizes, which invites future studies to profit from valuable insights from mixed methods research designs. Additionally, further investigation is required to delve into the strategies employed by Colombian learners in different language skills and subsystems.